Medicos: knowledge and attitude on Nipah at Malappuram district, India - Binub, Kanniyan (International Journal Of Community Medicine And Public Health, 2019)
Background: A recent epidemic of Nipah virus affected few districts of Malabar in Kerala, Southern India. Eighteen people died, remarking case fatality rate of 94.7%. Early diagnosis within second case by doctors and prompt control activities by the health ministry saved more lives. Objective was to study knowledge and attitude about Nipah among medical students of Malappuram District. Methods: The study was conducted among 200 MBBS students of tertiary medical college at Malappuram district, North Kerala. A pre structured questionnaire was used to study on knowledge and attitude related to Nipah among medical. Then the data was collected, analyzed and entered into Excel. The frequency of awareness among medical students was expressed in proportions. Results: Majority had good attitude and half of them had good knowledge about the disease. Most of students have been aware about the virus by social media (40.5%) as major source of information followed by news/newspaper (34%), (17.5 %) internet and (8%) by awareness programs. Conclusions: Topic about Nipah virus disease should be inculcated in medical textbooks elaborately. Special training programs for medical students should be on focus and health education sessions should be enhanced.